2022
DOI: 10.1590/0034-7167-2021-0562
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a rehabilitation nursing program for fragile elderly

Abstract: Objective: To build a rehabilitation nursing program to be implemented in the homes of frail elderly people and validate it by rehabilitation nurses. Methods: This is a qualitative, exploratory study, divided into two stages. The first corresponded to an integrative literature review that supported the construction of the program. The second consisted of the program content validity stage, through a focus group, in May 2021. Results: Nine experts participated in the construction and content validation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(47 reference statements)
0
2
0
1
Order By: Relevance
“…Deve ainda considerar-se que a utilização de polifármacos, possuir doenças cardiovasculares e diabetes mellitus prejudicam a velocidade, alteram a base de sustentação e a cadência da marcha em idosos (17,23) . Neste sentido, conceber e implementar programas de reabilitação para a população idosa focados no equilíbrio e na marcha, tem como resultados a atenuação, ou pelo menos a preservação das capacidades de andar e equilibrar-se (9,11,24) .…”
Section: Discussionunclassified
“…Deve ainda considerar-se que a utilização de polifármacos, possuir doenças cardiovasculares e diabetes mellitus prejudicam a velocidade, alteram a base de sustentação e a cadência da marcha em idosos (17,23) . Neste sentido, conceber e implementar programas de reabilitação para a população idosa focados no equilíbrio e na marcha, tem como resultados a atenuação, ou pelo menos a preservação das capacidades de andar e equilibrar-se (9,11,24) .…”
Section: Discussionunclassified
“…Following a consistent practice with theoretical nursing frameworks [10], SNRNs, focused on the developmental or health/illness transitions experienced by people, are in a privileged position to promote health literacy, ensuring better use of health services, greater ease of communication with health professionals, and better adherence to preventive behaviours and attitudes. Aware of the impact of self-care actions (the main focus of their intervention) on health status, these specialist nurses have been investing in empowering people to manage their health projects, delaying, through health promotion actions, the onset of complications associated with pathological processes and/or the aging process itself [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In studies that have been carried out in the country, especially with older people [11,13,14], SNRNs have found that an investment in health literacy in earlier age groups would have the potential to prevent some complications later in life. In Portugal, although such investment is being made, namely among the child and adolescent population [15,16], weaknesses are denoted in adulthood.…”
Section: Introductionmentioning
confidence: 99%